Turning up the heat: warming oceans and their effect on armed conflict in the Philippines (2021)
Marine ecosystems are particularly vulnerable to changes in climatic variables, making fishing livelihoods highly risky in times of global climate emergency. In fact, the collapse of some fish stocks because of increasing water temperatures is starting to become evident. In the Philippines, rural and poor fishing communities have highly extorsive relationships with non-state armed actors, making them even more vulnerable. Using sea surface temperature, conflict, and fisheries production data for the years 2003-2018, this paper examines the impact of sea surface temperature shocks on armed conflict-related violence in the 64 provinces with a coastline in the Philippines. The results are conclusive to a positive and statistically significant effect of sea surface temperature shocks on conflict-related outcomes such as number of violent events and deaths associated with them. This effect is driven by the negative impacts of these deviations on both agricultural and fisheries production. Using information on the dynamics of armed...